Volcanic Radiative Forcing From 1979 to 2015. Issue 22 (19th November 2018) - Schmidt, Anja; Mills, Michael J.; Ghan, Steven; Gregory, Jonathan M.; Allan, Richard P.; Andrews, Timothy; Bardeen, Charles G.; Conley, Andrew; Forster, Piers M.; Gettelman, Andrew; Portmann, Robert W.; Solomon, Susan; et al.
Abstract: Using volcanic sulfur dioxide emissions in an aerosol‐climate model, we derive a time series of global‐mean volcanic effective radiative forcing (ERF) from 1979 to 2015. For 2005–2015, we calculate a global multiannual mean volcanic ERF of −0.08 W/m 2 relative to the volcanically quiescent 1999–2002 period, due to a high frequency of small‐to‐moderate‐magnitude explosive eruptions after 2004. For eruptions of large magnitude such as 1991 Mt. Pinatubo, our model‐simulated volcanic ERF, which accounts for rapid adjustments including aerosol perturbations of clouds, is less negative than that reported in the Intergovernmental Panel on Climate Change (IPCC) Fifth Assessment Report (AR5) that only accounted for stratospheric temperature adjustments. We find that, when rapid adjustments are considered, the relation between volcanic forcing and volcanic stratospheric optical depth (SAOD) is 13–21% weaker than reported in IPCC AR5 for large‐magnitude eruptions. Further, our analysis of the recurrence frequency of eruptions reveals that sulfur‐rich small‐to‐moderate‐magnitude eruptions with column heights ≥10 km occur frequently, with periods of volcanic quiescence being statistically rare. Small‐to‐moderate‐magnitude eruptions should therefore be included in climate model simulations, given the >50% chance of one or two eruptions to occur in any given year. Not all of these eruptions affect the stratospheric aerosol budget, but those that do increase the nonvolcanic background SAOD by 0.004 on average, contributing 50% to the total SAOD in the absence of large‐magnitude eruptions. This equates to a volcanic ERF of about −0.10 W/m 2, which is about two thirds of the ERF from ozone changes induced by ozone‐depleting substances. Plain Language Summary: We calculate the climatic effects of explosive volcanic eruptions between 1979 and 2015 using a more complex climate model simulation than has been used previously. This includes many of the chemical and physical processes that lead to the formation of volcanic aerosol. Volcanic aerosols are tiny airborne particles that are important for Earth's climate because they reflect sunlight and trap thermal infrared radiative energy. In line with previous studies, we find that the most powerful eruptions between 1979 and 2015 had a substantial cooling effect. However, we calculate that their effect on climate is about 20% weaker than previous estimates used by the Intergovernmental Panel on Climate Change (IPCC). In our model simulation this is mainly a result of the volcanic aerosol particles affecting ice clouds, making these clouds less transparent. We also find that it is very rare to have a period with relatively few notable explosive eruptions as was the case during 1996–2002. Furthermore, eruptions of small‐to‐moderate size occur frequently and decrease the transparency of the stratosphere by as much as all nonvolcanic sources of aerosol particles combined. These small‐sized volcanic eruptions therefore cause a small but noticeable surface cooling and so should be included in climate model simulations, which is rarely done. Key Points: Small‐magnitude eruptions caused a global‐mean ERF of −0.08 W/m 2 during 2005–2015 relative to the volcanically quiescent 1999–2002 period In our model rapid adjustments act to reduce the total volcanic forcing per unit SAOD change by 13–21% for large‐magnitude eruptions On average, frequent small‐magnitude eruptions increase the nonvolcanic background SAOD by 0.004, equating to a volcanic ERF of −0.10 W/m 2